2012
DOI: 10.2967/jnumed.112.104117
|View full text |Cite
|
Sign up to set email alerts
|

11C-Hydroxytryptophan Uptake and Metabolism in Endocrine and Exocrine Pancreas

Abstract: Determination of the residual b-cell mass using noninvasive tools might help to follow up the efficacy of new treatments in both type 1 (insulin-dependent) and type 2 (non-insulin-dependent) diabetes mellitus, including islet transplantation. b-cells are neuroendocrine cells that can take up and metabolize the serotonin precursor 5-hydroxytryptophan. The serotonin pathway may therefore be an attractive target for the development of an imaging tracer for residual b-cell mass. The aim of this study was to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…Thus, the findings by Di Gialleonardo et al (10) in the PANC1 cell line may not be representative for higher species such as nonhuman primates or humans.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Thus, the findings by Di Gialleonardo et al (10) in the PANC1 cell line may not be representative for higher species such as nonhuman primates or humans.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, the uptake was similar in magnitude in a and b cells, but the retention in b cells was higher, resulting in an increased relative accumulation in b cells 60 min after intravenous administration with 75% of the tracer found within the b cells (9). Di Gialleonardo et al (10) performed in vitro uptake studies using the ductal cell line PANC1 as a model for exocrine tissue. They showed that accumulation in PANC1 cells was comparable to that of INS-1 cells but not mediated by normal serotonergic metabolism because the accumulated tracer metabolite was resistant to degradation by MAO-A.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Radiolabeled 5-HTP therefore accumulates in the form of serotonin in islets of Langerhans as opposed to the exocrine pancreatic parenchyma (9,22). In vitro studies of [ 11 C]5-HTP show high selective retention (8-55 times) in human islets compared with exocrine cells (18).…”
mentioning
confidence: 99%